Educação e linguagem desde a enunciação oral do professor de língua inglesa : autopercepção e percepção de alunos - Schulz, Lisiane Ott (My University, 2014)
The purposes of this investigation were: (a) to verify how effective was students’ understanding of a teacher’s speech considering the B2 English proficiency level (according to the classification suggested in the Common European Framework document) and (b) to identify teachers’ and students’ perceptions on how a teacher’s classroom speech should be delivered so as to help B2 students improve their listening comprehension skills in an effective way. Based on these data, teachers’ and students’ perceptions were compared. Furthermore, a contrastive analysis between their beliefs and the didactics purpose of the teacher’s speech was also carried out. The general hypothesis that drove this study is that most teachers and most B2 proficiency level students believe that a teacher’s speech should be delivered so as to facilitate students’ understanding and that this helps students improve their listening comprehension skills. The data were collected through (1) a listening comprehension questionnaire given to students right after they listened to the recording of a teacher’s speech and (2) survey questionnaires that investigated the subjects’ perceptions regarding different features of teachers’ speech such as speech rate, use of unfamiliar words, expressions and syntactic structures, use of mother tongue and intonation. The data was analyzed from a Vygotskian perspective, from Ausubel’s meaningful learning concept and from Benveniste’s and Bakhtin’s views of language. As the data analysis showed, most students and teachers believe that the teacher’s speech should be delivered in such a way as to facilitate students’ understanding. It also revealed that these beliefs were reflected in the teacher’s classroom practice. Moreover, the results suggested that most teachers do not seem to correlate the way a teacher’s speech is delivered to the possibility of this helping improve students’ listening comprehension skill.
Esta investigação teve como objetivos: (a) verificar o grau de êxito da compreensão do discurso oral docente de aprendizes de língua inglesa de nível de proficiência B2, conforme classificação sugerida pelo Quadro Comum Europeu; e (b) identificar as percepções de professores e alunos de cursos desse mesmo nível a respeito de como deve ser a enunciação oral docente, com vistas à promoção efetiva do desenvolvimento da habilidade de compreensão oral dos aprendizes. A finalidade deste estudo foi a de comparar a percepção dos dois grupos, bem como contrastar essas opiniões com a finalidade didática da enunciação. Tomamos por base a hipótese geral de que a maioria dos professores e alunos de nível B2 de proficiência acredita que a enunciação oral docente deva ser apresentada de forma a facilitar a compreensão do aprendiz e que isso promove o desenvolvimento da habilidade de compreensão oral por parte deste último. Os dados foram coletados por meio de: (1) um questionário de verificação da compreensão oral, aplicado aos alunos logo após a audição da gravação do discurso de um professor; (2) questionários aplicados a professores e alunos sobre suas percepções quanto a diferentes aspectos da enunciação oral docente, tais como velocidade de fala, frequência de uso de léxico e estruturas sintáticas não familiares ao aluno, uso da língua materna e entonação. A análise e discussão dos dados foram realizadas à luz da teoria sociointeracionista, de Vygotsky, do conceito de aprendizagem significativa, de Ausubel, e das teorias enunciativas de Benveniste e Bakhtin. Os dados apontam para o fato de, tanto alunos quanto professores, acreditarem que o discurso docente deva ser apresentado de forma a facilitar a compreensão oral discente e que essa crença reflita-se na prática do professor; também indicam que a maioria dos professores não parece relacionar a forma como o discurso oral docente é proferido à possibilidade de isso auxiliar no desenvolvimento da habilidade de compreensão discente.
Keywords: Língua inglesa - Estudo e ensino; Foreign language teaching and learning; Students’ oral comprehension